The choice of exchange rate regimes: An empirical analysis for transition economies - Jürgen von Hagen; Jizhong Zhou (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
We analyze the choice of exchange rate regimes of the 25 transition economies in Europe and the CIS after 1990. The empirical results show that the traditional Optimum Currency Area considerations provide relevant guidance for the exchange rate regime choices in these countries. Moreover, regime choices are influenced by inflation rates, cumulative inflation differentials, and the availability of international reserves. That is, macroeconomic stabilization and the ability to commit to a credible exchange rate peg play important roles in the determination of exchange rate regime choices. Large government deficits have ambiguous effects; they increase the likelihood of moving from a flexible exchange rate to an intermediate peg as well as the likelihood of moving from a fixed to an intermediate peg.
Keywords: 330